THE BRAZILIAN PEPPER MARKET AND THE IMPACTS OF EXPORTS IN THE COVID-19 PANDEMIC - Niculau, Daiane Morato; Ferrarezi Junior, Niculau (Revista Interface Tecnológica, 2022)
During the COVID-19 pandemic, the world suffered several impacts, among them what affected the economy considerably. The agricultural market felt the reflection of the moment and some products either had their prices high due to the rise in dollar values, or suffered a drop in consumption due to the decrease in purchasing power, as many people became unemployed. Pepper in its varieties is a product that has shown a growing market, a factor arising from its benefits and varieties of by-products that reach the consumer's table. Within this reality, the objective of this study is to show the pepper market in the context of the pandemic, a factor of great importance since it is a culture that comes from the work of family farming. The methodology used was a bibliographic review, where articles and websites that discuss the focus of this study were consulted. The results show that the Brazilian pepper market in two varieties showed growth at the time of the pandemic.
Keywords: Agribusiness; Family farming; Export